Preliminary assessment of small scale bacterial depuration of Crassostrea gigas and Anadara spp., Gulf of Nicoya, Costa Rica - Vega-Corrales, Luis A.; Marín-Vindas, Carolina; Pacheco-Prieto, Oscar; Zúñiga-Calero, Gerardo (Revista Ciencias Marinas y Costeras, 2013)
Bivalve molluscs are sold without any sanitary control in Costa Rica, which represents a public health risk due to the possible accumulation of pathogenic bacteria. Small scale bacterial depuration treatments were preliminarily evaluated on Crassostrea gigas and Anadara spp. from the Gulf of Nicoya, Costa Rica, through the use of a recirculating system with UV irradiation. The levels of Escherichia coli in the water were determined using the MPN method. The MPN of E. coli and the presence of Salmonella spp., Vibrio parahaemolyticus and V. cholerae were determined in molluscs. Results confirm the effectiveness of the E. coli depuration system design in C. gigas and Anadara spp. The MPN of E. coli in the molluscs was reduced between 79% and 100% after 24 h. None of the other types of bacteria were found in the samples analyzed. This is the first C. gigas depuration study in Costa Rica and the first report concerning UV depuration for bacterial indicators of fecal contamination in Anadara spp. This research serves as a basis for the implementation and improvement of mollusc purification conditions in the country. It is recommended to monitor extraction and harvesting areas, as well as to implement the depuration of bivalve molluscs so that traditional producers can offer an innocuous product with added value.